2023
DOI: 10.3390/vaccines11030631
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils in Mycobacterium tuberculosis

Abstract: Mycobacterium tuberculosis (M. tb) continues to be a leading cause of mortality within developing countries. The BCG vaccine to promote immunity against M. tb is widely used in developing countries and only in specific circumstances within the United States. However, current the literature reports equivocal data on the efficacy of the BCG vaccine. Critical within their role in the innate immune response, neutrophils serve as one of the first responders to infectious pathogens such as M. tb. Neutrophils promote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 70 publications
3
9
0
Order By: Relevance
“…The immune infiltration analysis demonstrated that macrophages (M1, M2), monocytes, NKTs, neutrophils, Tregs cells, and plasma cells had higher numbers in TB samples in both datasets, which corroborated previous studies [45][46][47][48][49][50]. Human M1 macrophages express unique innate immune response genes after mycobacterial infection to defend against TB, while M2 macrophages have an inhibitory effect on immune responses, inhibiting antigen presentation and T-cell proliferation, exerting anti-inflammatory responses, attenuating cellular immunity against TB infection, and thereby promoting chronic TB infection [51,52].…”
Section: Discussionsupporting
confidence: 90%
“…The immune infiltration analysis demonstrated that macrophages (M1, M2), monocytes, NKTs, neutrophils, Tregs cells, and plasma cells had higher numbers in TB samples in both datasets, which corroborated previous studies [45][46][47][48][49][50]. Human M1 macrophages express unique innate immune response genes after mycobacterial infection to defend against TB, while M2 macrophages have an inhibitory effect on immune responses, inhibiting antigen presentation and T-cell proliferation, exerting anti-inflammatory responses, attenuating cellular immunity against TB infection, and thereby promoting chronic TB infection [51,52].…”
Section: Discussionsupporting
confidence: 90%
“…However, arginase was more highly expressed in groups 1 and 3 than in group 2. Neutrophils are the first defense against bacteria and perform phagocytosis, degranulation and nuclear material release functions in the form of extracellular neutrophil traps (NETs) [ 54 , 55 ]. Arginase-1, released by neutrophil granules, degrades arginine by an immunoregulatory homeostatic mechanism [ 56 ], causing inhibition of cytokine production by NK cells.…”
Section: Discussionmentioning
confidence: 99%
“…In the oxygen‐independent killing pathway, neutrophil granules also play a crucial role in inhibiting or killing MTB 27 . Cationic proteins, defensins, and permeability proteins are the major bactericidal substances, working by direct contact with MTB to eliminate it 28 . Furthermore, activated neutrophils secrete various chemotactic factors, such as IL‐8, CXCL8, CXCL1, CXCL10, and CXCL11, which amplify their own recruitment and directed chemotaxis, synergistically working with other immune cells to enhance phagocytosis and bactericidal functions, thus enhancing the host's killing effect on MTB 29,30 …”
Section: Immunologic Mechanisms Of Mtb–host Interactionsmentioning
confidence: 99%